Hubungan Tingkat Pengetahuan Dengan Kesiapan Menghadapi Menopause Pada Wanita Usia Pre Menopause Di Desa Bengbulang Kecamatan Karangpucung Kabupaten Cilacap - Yulianawati; Diah Atmarina Y (2026)
Menopause is a natural biological process experienced by all women, marked by the permanent cessation of menstruation. Women go through several stages, including premenopause, perimenopause, menopause, and postmenopause. Lack of knowledge about menopause can lead to anxiety and stress, particularly in premenopausal women. A preliminary study revealed that most premenopausal women in Bengbulang Village had limited understanding and were unprepared for menopause. Objective, this study aims to examine the correlation between knowledge level and readiness for menopause among premenopausal women in Bengbulang Village, Karangpucung Sub-district, Cilacap Regency.Methods: This quantitative research used a correlational analytic design. The sample consisted of 62 respondents selected through purposive sampling. Data analysis was conducted using the Spearman Rank test. Results, the results showed a significant correlation between knowledge level and readiness for menopause (p = 0.001).Conclusion: There is a statistically significant correlation between knowledge level and readiness to face menopause among premenopausal women.